Development of the yolk nucleus of previtellogenic oocytes in rainbow trout, Oncorhynchus mykiss, studied by light microscopy - (:unkn) unknown (My University, 2007)
0

In this study, the development of the yolk nucleus in cytoplasm of previtellogenic oocytes was examined by light microscopy during oogenesis in trout, Oncorhynchus mykiss. We determined that oocytes 20-30 um in diameter have much basophilic (electron dense) cytoplasm and an area of flocculent appearance begins to emerge around the nucleus. The yolk nucleus was first recognized within this area as a few fragments dense granular thread. These fragments were observed gradually increase in number and length until they assemble into a spherical mass. When oocytes develop to greater than 107 um in diameter, the yolk nucleus was dispersed throughout the cytoplasm and the cytoplasm was observed more homogenous.
Keywords: Biyoloji